Effects of feeding copper and feed-grade antimicrobials on the growth performance of weanling pigs - Amachawadi, R.G.; Shelton, N.W.; Tokach, Michael D.; Scott, Harvey Morgan; DeRouchey, Joel M.; Nagaraja, Tiruvoor G.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
A total of 240 weanling pigs (34 d of age with an average body weight of 17.1 lb) were used in a 35-d growth trial to compare the growth performance effects of copper (Cu) and feed-grade antimicrobials. The 6 dietary treatments were arranged in a 2 × 3 facto- rial with 2 added Cu levels (basal level of 16.5 ppm or basal + 125 ppm from copper sulfate) and 3 antimicrobial treatments including a control, chlortetracycline (CTC; Alpharma, Fort Lee, NJ) at 500 g/ton (10 mg/kg BW), and tylosin (Tylan; Elanco Animal Health, Greenfield, IN) at 100 g/ton. Each treatment had 8 pens with 5 pigs per pen. Treatments were allotted to pen in a randomized complete block design, with location within the barn serving as the blocking factor. Following the brief acclimatization period prior to starting the experiment (13 d), pigs were fed dietary treatments for 21 d followed by another 14 d on the control diet to examine any carryover effects. No significant copper × antimicrobial interactions were observed (P > 0.07) for any pig performance response. From d 0 to 21, pharmacological Cu tended to increase (P < 0.07) both ADG and ADFI compared with pigs provided basal levels of Cu. Dietary CTC inclusion increased (P < 0.01) ADG and tended to improve (P < 0.09) ADFI and F/G over pigs not fed diets with CTC. Dietary Tylan did not alter (P > 0.19) ADG, ADFI, or F/G compared with pigs provided the control diets. From d 21 to 35, pigs that previously had received pharmacological Cu tended to have lower (P < 0.06) ADG compared with those never receiving pharmacological Cu. Also, pigs previously receiving Tylan had lower (P < 0.01) ADG than those never receiving Tylan. For the overall trial (d 0 to 35), adding Cu for the first 21 d had no impact (P > 0.32) on ADG, ADFI, or F/G. Similarly, Tylan did not influence (P > 0.30) pig performance. The benefits of CTC during the first 21 d led to a tendency for increased (P < 0.06) ADG and ADFI compared with those not receiving CTC. Overall, pharmacological Cu and antimicrobials may offer performance advantages when incorporated in nursery pig diets; however, that advantage will not increase and may be lost after Cu and/or antimicrobials are removed from diet.
Keywords: Swine; Nursery pig; Antimicrobials; Copper; Growth promoters